Implementasi Kurikulum Muatan Lokal Berbasis Akhlak di Kabupaten Bangka Tengah - Suparta, Suparta (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Moral Education is the key to the success of education as a whole, both in the household, school, and community. During this time, a child is often only equipped with religious knowledge in the form of cognitive, while the inculcation of the foundations of faith is merely a slogan, an expression without reality. As a result, children have a lot of knowledge and intelligent brains, but have behaviors that are not in accordance with their knowledge. For this reason, the teachings of Islam should not be used as objects that are only studied and understood and memorized. However, the teachings of Islam must be subject to be understood, memorized and practiced. In fact, the tendency of teenagers today is to prioritize materialist and hedonic orientations, so that they are morally and spiritually poor. Thus the morality possessed is not an Islamic personality but an instant personality that he gets from the guidance of a misleading spectacle. To realize this expectation, there must be a local curriculum based on Akhak.